PERSISTENSI KINERJA REKSA DANA SAHAM DI BURSA EFEK INDONESIA - Dimas Rahmat Wijaya; Dedi Rusdi (Universitas Islam Sultan Agung (UNISSULA), Faculty of Economics, Department of Accounting, 2014)
Investors are required to be more prudent in determining the investment option since many choices For investing in a mutual funds are popped . So some research is needed to review the performance of mutual funds that active in Stock exchange to be a reference in predicting the performance of mutual funds next year. This research use data from the beginning of the period 2007 until the end of 2012 or from the beginning of the global crisis period and during the crisis period is underway , it is expected to provide accurate results as a benchmark to invest in mutual funds . Because nowaday, the development of the capital markets is used by firms to raise funds from the public . The results of this study showed the presence of persistence in the performance of quarterly, semi annually, annually and biennial mutual fund shares at the Indonesia Stock Exchange . While the monthly and triennial performance of mutual fund shares in Indonesia Stock Exchange did not persistence.